Who is minding the kids? New developments and lost opportunities in reforming the British early education workforce - Ludovica Gambaro (Journal of European Social Policy, 2017)
The last 200.167emyears have seen a substantial increase in enrolment in early childhood education and care (ECEC) in several European countries. The expansion of ECEC services inevitably requires new staff. There is however a tension between a rapid growth of services via the creation of low-paid, low-qualified jobs and the aspiration, voiced unanimously by policy makers, to improve the qualification and status of ECEC workers. This paper examines the case of the UK, where ECEC services and public expenditure devoted to them have increased substantially. It uses UK Labour Force Survey data to document changes in the pay and educational qualifications of the early education workforce. Results show how despite a general increase in the qualification level of these workers, their pay remains relatively low. Moreover, pay is found to be mostly related to characteristics of the workplace, and its access to public funding, rather than to the productive characteristics of workers. The paper concludes by arguing that the issue of low pay in ECEC is likely to become more salient in the future, as governments expand services while trying to keep down their costs.
Keywords: 330; early childhood education and care; ECEC quality; employment conditions; low pay; vocational qualities